The analysis of a condition of professional training of future ecologists in the system of higher education - Dlimbetova, G.K.; Aliyeva, A.; Kultan, J.; Akeshova, M.M. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
Ecological education becomes a subject of interest and action of the international organizations at the highest level. The search of harmonious interaction of society and nature leads to an intensive process of ecologization of general culture of mankind. It is caused by the need for increase of people’s susceptibility and their involvement degree in the solution search of development problems and preservation of the surrounding environment. On the global and universal value, ecological education is specified as the main means of constructive transformation of social and individual ecological consciousness almost at all international forums about the environment problems. Many of them are actually devoted to ecological education since the condition of the surrounding environment, the general ecological education of all population depends on the level of professional competency of future ecologist.
Жоғарғы білім беру жүйесінде болашақ экологтарды кəсіптік дайындаудың талдау шарттары
Анализ условия профессиональной подготовки будущих экологов в системе высшего образования
Keywords: professional training; the system of higher education; future ecologists